Políticas Públicas de informação científica: o portal de periódicos da Capes na UFCA - Mendonça, Glacinésia Leal (2014)
This study involves the use of Portal de Periódicos da CAPES by the students of Federal University of Cariri, Campus de Juazeiro, State of Ceará, Brazil. Through exploratory and descriptive case study, the use of this tool is analyzed by student profile characteristics and the effects of actions of the global and local public information policies such as implementation, divulgation and user training. Indeed, the research reassures the portal as the main scientific database available for the Brazilian academic community, and, at local level, the unique institutional tool for scientific publications. Also it highlights that the majority of respondents indicated that they know about the existence of the portal, although this fact does not ensure and effective retrieval and use of information. As main reasons that encourage the use, this study shows the role of the professors, especially due to academic obligations. As limitations of use, this research indicates the student’s linguistic incompetence to deal with texts in other languages, and the lack of ability to perform appropriately on searching for information, caused mainly by the insufficient educational actions on users training. In spite of the lacking training situation, it found out that the library is the main provider of the existing training actions. Finally, the research concludes that there is a long way to put the academic community, especially students, in the current patrons of access of scientific information, a task that will demand more education actions of users provided by library in cooperation with the others segments of the university, such as professors.